Implementasi Augmented Reality Pada Pembelajaran IPA Siswa SMP - Suharjanto Utomo; Samsul Budiarto; Iswanto Iswanto; Sofyan Ibnu Abdillah; Wilson Ilhamdi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In the learning process at the inclusive junior high school SMP Muhammadiyah 5 in the city of Cimahi, conventional methods are still employed, utilizing limited book resources, and students remain passive, merely listening to what the teacher imparts. Augmented Reality is a technology that combines the real world with digital or virtual elements, creating an engaging and interactive user experience. The purpose of this research is to develop a learning media using Augmented Reality technology that is engaging and interactive in the field of Science, thus facilitating both teachers and students in comprehending the material. The stages in this research employ the Multimedia Life Cycle method, which includes concept, design, data collection, creation, testing, and distribution. The research has successfully developed an Android-based application that has undergone black box testing. Survey results also indicate a 90% satisfaction rate, demonstrating that the application is easy to use, interactive, and engaging.